Gambaran Keamanan Makanan dan Nilai Gizi pada Menu Maincourse Ikan Woku Belanga di PT. Aerofood Indonesia Unit Denpasar (International Forum of Researchers and Lecturers, 2024)
The provision of in-flight catering services is a crucial component in ensuring a high-quality flying experience, guaranteeing food safety and nutritional balance to support passenger health during flights. PT. Aerofood Indonesia Denpasar is committed to being an internationally recognized catering company that provides a diverse range of meals, including Asian cuisine, Japanese/Korean cuisine, Western cuisine, Nusantara and local cuisine, pastry and bakery products for airline passengers. One of the most frequently produced main dishes is Woku Belanga Fish.This study aims to provide a comprehensive overview of the importance of food safety implementation and nutritional analysis in the in-flight catering industry. The research employs a qualitative approach through observations and interviews. Food safety assessment is conducted by determining Critical Control Points (CCPs) at each stage, from raw material reception to distribution to the aircraft. The majority of product descriptions align with the Indonesian National Standard (SNI) 01-4852-1998. Laboratory examination of the Ikan Woku Belanga dish revealed a total plate count (TPC) of 1.1 × 10⁴ CFU/g, with no detectable levels of Enterobacter, Escherichia coli, Staphylococcus aureus, or Bacillus cereus. In terms of its nutritional value, when served as a lunch option for midday flights, the Woku Belanga Fish dish meets 61.5% of the energy requirement, 85.5% of protein, 60.5% of fat, and 54.7% of carbohydrates, based on an adult daily energy requirement of 2,150 kcal.